MACROFAUNA NA AGRICULTURA FAMILIAR DA ALDEIA INDÍGENA DE PORTO LINDO, JAPORÃ -MS - AGUIAR, Allan Kardec Moreira; MARTINS, Gledson; CASTILHO, Selene Cristina de Pierri; MARRA, Leandro Marciano (ANAIS DO ENIC, 2018)
-